Blocky Sb/C Anodes with Enhanced Diffusion Kinetics for High‐Rate and Ultra‐Long Cyclability Sodium Dual‐Ion Batteries. Issue 18 (21st August 2021) - Li, Hong‐Ji; Li, Jing‐Jing; Chen, Zhe; Wang, Zhen‐Zhen; Qu, Jin; Chen, Yi‐Qian; Zhu, Li‐Jun; Jiang, Fei
Abstract: Sodium ion‐based dual ion batteries (SDIBs) have attracted increasing attentions for their high operative voltages and low cost, but their poor long‐term cycling stability and rate capability largely hinder their practical applications. Here, an optimized anode‐antimony/carbon/graphene (Sb/C/G) composite for SDIBs is designed. Sb nanoparticles (NPs) not only can enhance the specific capacity but also facilitate the Na + diffusion kinetics. The continuous conductive carbon matrix can promote the electron transfer process and accommodate volume changes of Sb NPs during sodiation/desodiation. Therefore, superior electrochemical performance, for example, a high discharge capacity of 376 mA h g −1 with a higher ICE (69.1 %) at current density of 500 mA g −1, an excellent cycling stability (73 mA h g −1 is retained even after 1400 cycles at current density of 1000 mA g −1 ), and high stable CE of 99.0 %. Our study offers a suitable design for Na + ‐based batteries anode structure and accelerates their practical applications. Abstract : Blocky road : Sodium dual‐ion batteries (SDIBs) with Sb/C/G anode and expanded graphite (EG) as cathode, NaClO4 as salts can deliver superior electrochemical performance, for example, a high discharge capacity of 376 mA h g −1 with a higher ICE (69.1 %) at current density of 500 mA g −1, a excellent cycling stability (73 mA h g −1 is retained even after 1400 cycles at current density of 1000 mA g −1 ), and high stable CE of 99.0 %.